INTELLECTUAL CAPITAL DISCLOSURE IN BANKING COMPANY AT INDONESIA STOCK EXCHANGE - Wijayanti, Calvina; Purwanto, Adriana Marini; Dwijayanti, S. Patricia Febrina (Fakultas Bisnis Universitas Katolik Widya Mandala Surabaya, 2019)
Intellectual capital is one of intangible asset’s component that can provide an added value to the company. Intellectual capital disclosure in the company’s annual reports can help to provide a complete information for investors in predicting the performance of the company for making an economic decisions. In addition, intellectual capital disclosure can also show the good performance of a company to attract investors. Intellectual capital disclosure can be affected by several factors, such as leverage, profitability, company age, and listing age. This study aims to obtain empirical evidence and analyze the effect of leverage, profitability, company age, and listing age on intellectual capital disclosure. The sample used in this study are banking companies listed in Indonesia Stock Exchange. The number of samples in this study are 95 companies and selected using purposive sampling. Hypothesis testing are using multiple linear regression analysis. Based on the results of the hypothesis testing, the results of this study show that profitability, company age, and listing age have a significant positive effect on intellectual capital disclosure, while leverage have no significant effect on intellectual capital disclosure.